Possible Association of Polymorphisms in Ubiquitin Specific Peptidase 46 Gene With Post-traumatic Stress Disorder - Seo, Jun Ho; Kim, Tae Yong; Kim, Se Joo; Choi, Jin Hee; So, Hyung Seok; Kang, Jee In (Frontiers in Psychiatry, 2021)
Introduction: Dynamic proteolysis, through the ubiquitin-proteasome system, has an important role in DNA transcription and cell cycle, and is considered to modulate cell stress response and synaptic plasticity. We investigated whether genetic variants in the ubiquitin carboxyl-terminal hydrolase 46 (USP46) would be associated with posttraumatic stress disorder (PTSD) in people with exposure to combat trauma using a case-control candidate gene association design. Methods: Korean male veterans exposed to the Vietnam War were grouped into those with (n = 128) and without (n = 128) PTSD. Seven tagging SNPs of USP46 were selected, and single-marker and haplotype-based association analyses were performed. All analyses were adjusted for sociodemographic factors and levels of combat exposure severity and alcohol problem. Results: One single-marker (rs2244291) showed nominal evidence of association with PTSD status and with the ‘re-experiencing’ cluster, although the association was not significant after Bonferroni correction. No significant association with the other SNPs or the haplotypes was detected. Conclusion: The present finding suggests preliminarily that genetic vulnerability regarding the ubiquitin-proteasome system may be related to fear memory processes and the development of PTSD symptoms after trauma exposure. Further studies with a larger sample size will be needed to examine the role of the ubiquitin-proteasome system including USP46 in PTSD.